(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2019)
The high number of broken eggshells on laying hens in Indonesia is very detrimental to farmers, so that needs to be overcome. A total of 480 Lohman chickens with 40 weeks of age were divided into 4 treatment groups with the addition of different doses of Avizyme® 1502 respectively P0 as a control that got 0 g/Kg of feed, P1 got 1 g/Kg of feed, P2 got 2 g/Kg of feed, P3 got 3 g/Kg of feed. Avizyme® 1502 contains enzymes xylanase, amylase, and protease. This treatment was given daily for 30 days. The sampling of eggshell checking was recorded when start of administering enzymes to the end of the administration and at the end of the study, 6 eggs from each treatment were taken randomly to measure the protein level. The results showed that the addition of 1 g/Kg of Avizyme® 1502 on feed provided the highest protein level in eggs. During the research period, eggs produced by the groups of chicken under treatments of Avizyme 1502® showed a decrease in cracked eggshell.